Heavy water additive in formamidinium : a novel approach to enhance perovskite solar cell efficiency - Solanki, Ankur (2020)
Heavy water or deuterium oxide (D2O) comprises deuterium, a hydrogen isotope twice the mass of hydrogen. Contrary to the disadvantages of deuterated perovskites, such as shorter recombination lifetimes and lower/invariant efficiencies, the serendipitous effect of D2O as a beneficial solvent additive for enhancing the power conversion efficiency (PCE) of triple‐A cation (cesium (Cs)/methylammonium (MA)/formaminidium (FA)) perovskite solar cells from ≈19.2% (reference) to 20.8% (using 1 vol% D2O) with higher stability is reported. Ultrafast optical spectroscopy confirms passivation of trap states, increased carrier recombination lifetimes, and enhanced charge carrier diffusion lengths in the deuterated samples. Fourier transform infrared spectroscopy and solid‐state NMR spectroscopy validate the N–H2 group as the preferential isotope exchange site. Furthermore, the NMR results reveal the induced alteration of the FA to MA ratio due to deuteration causes a widespread alteration to several dynamic processes that influence the photophysical properties. First‐principles density functional theory calculations reveal a decrease in PbI6 phonon frequencies in the deuterated perovskite lattice. This stabilizes the PbI6 structures and weakens the electron–LO phonon (Fröhlich) coupling, yielding higher electron mobility. Importantly, these findings demonstrate that selective isotope exchange potentially opens new opportunities for tuning perovskite optoelectronic properties.